In silico studies, X-ray diffraction analysis and biological investigation of fluorinated pyrrolylated-chalcones in zebrafish epilepsy models - Muhammad Syafiq, Akmal Mohd Fahmi; Swain, Puspanjali; Amirah, Hani Ramli; Wan Norhamidah, Wan Ibrahim; Nur Atikah, Saleh Hodin; Noraini, Abu Bakar; Tan, Yee Seng *; Siti Munirah, Mohd Faudzi; Kim, Cheol-Hee (Elsevier, 2023)
Epilepsy is the third most common known brain disease worldwide. Several antiepileptic drugs (AEDs) are available to improve seizure control. However, the associated side effects limit their practical use and highlight the ongoing search for safer and effective AEDs. Eighteen newly designed fluorine-containing pyrrolylated chalcones were extensively studied in silico, synthesized, structurally analyzed by X-ray diffraction (XRD), and biologically and toxicologically tested as potential new AEDs in zebrafish epilepsy in vivo models. The results predicted that 3-(3,5-difluorophenyl)-1-(1H-pyrrol-2-yl)prop-2-en-1-one (compound 8) had a good drug-like profile with binding affinity to γ-aminobutyric acid receptor type-A (GABAA, − 8.0 kcal/mol). This predicted active compound 8 was effective in reducing convulsive behaviour in pentylenetetrazol (PTZ)-induced larvae and hyperactive movements in zc4h2 knockout (KO) zebrafish, experimentally. Moreover, no cardiotoxic effect of compound 8 was observed in zebrafish. Overall, pyrrolylated chalcones could serve as alternative AEDs and warrant further in-depth pharmacological studies to uncover their mechanism of action.